Comparative analysis of the library classification system between Al-Almawi and Dewey - Khairul Nizam Bin Zainal Badri (Universitas Islam Negeri Sumatera Utara, 2023)
This study involves a comparative analysis between the library management system developed by Melvil Dewey in 1876 and Abd Al-Basit bin Musa Al-Almawi (1502-1573 AD) better known as Al-Almawi who lived in the heyday of the Ottoman Dynasty in the 16th century. The library management system developed by Dewey can be considered dominant at the moment as it is widely used around the world. However, this system is said to have posed some difficulties in terms of maintenance as its field categories have been restricted and field overlap as there are several fields have been grouped in one class. The classification number becomes longer when there are new categories thus causing the process of access and storage to be very complex. To address the problem, this study seeks to examine the system developed by Al-Almawi to see if the system is able to deal with the problem either in terms of technical and development intellectuality. The objective of the study is to find out the characteristics of the system highlighted by Al-Almawi, identify the impact of the system from axiology point of view, and the suitability of the system in the information system management industry. This study uses a fully qualitative approach where the library method is chosen to collect data and information related to the classification and cataloguing system. The data were then analysed using a structuring approach while to conclude the findings of the study, a descriptive approach was used. The results of the study found that the system developed by Al-Almawi not only overcome the problems faced by Dewey Decimal Classification (DDC) users, but also give emphasis on manners to knowledge where the materials that contain knowledge should be glorified and arranged in scientific order, where the material with the most truth values will be placed to a higher position. The measure of truth is based on the source of revelation contained therein. Thus, it can be said that significantly, the system developed by Al-Almawi not only pleases work that requires physical nature and planning; but also, soul-blissful and double-oriented because every activity is connected directly to God. The relationship is formed due to the existence of the unity of mind and deed, which is always in the mould of the framework of Tawhid.